2019
DOI: 10.1002/ams2.442
|View full text |Cite
|
Sign up to set email alerts
|

The effect of standard and high dose of rikkunshito on achievement of enteral nutrition target in critically ill patients: a pilot randomized controlled trial

Abstract: Aim: Rikkunshito is a traditional Japanese medicine used for delayed gastric emptying in intensive care units in Japan. This study aimed to investigate whether standard-or high-dose rikkunshito can improve the achievement of enteral calorie target among critically ill adults. Methods: This open-label, single-center, pilot randomized controlled trial was carried out from March 2018 until December 2018 and enrolled critically ill adult patients requiring enteral nutrition by gastric tube for at least 5 days. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The effect of prokinetics on hospital length of stay was examined by five studies [ 23 , 25 27 , 29 ]. These five studies, which enrolled a total of 250 patients, showed a significant difference in the hospital length of stay between the prokinetic agent-treated group and the control group (MD -3.21, 95% CI -5.35, -1.06; P = 0.003; I 2 = 28%) ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of prokinetics on hospital length of stay was examined by five studies [ 23 , 25 27 , 29 ]. These five studies, which enrolled a total of 250 patients, showed a significant difference in the hospital length of stay between the prokinetic agent-treated group and the control group (MD -3.21, 95% CI -5.35, -1.06; P = 0.003; I 2 = 28%) ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…These five studies, which enrolled a total of 250 patients, showed a significant difference in the hospital length of stay between the prokinetic agent-treated group and the control group (MD -3.21, 95% CI -5.35, -1.06; P = 0.003; I 2 = 28%) ( Fig 2 ). Three studies evaluated the effect of prokinetics on ICU length of stay in the critical care setting [ 23 , 25 , 27 ]. These three studies, enrolling a total of 186 patients, showed that prokinetic agents appeared to have a positive effect on shortening ICU length of stay (MD -2.03, 95% CI -3.96, -0.10; P = 0.04; I 2 = 0%) ( Fig 3 ) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations